Antiplasmodial, Antitrypanosomal, and Cytotoxic Effects of Anthonotha macrophylla, Annickia polycarpa, Tieghemella heckelii, and Antrocaryon micraster Extracts - Aboagye Kwarteng Dofuor; Emmanuel Kofi Kumatia; Jersley Didewurah Chirawurah; Frederick Ayertey (Hindawi Limited, 2022)
Malaria and trypanosomiasis are protozoan diseases which pose a devastating challenge to human health and productivity especially, in Africa where their respective vectors (female Anopheles mosquito and tsetse fly) abound. Various medicinal plants are used to treat these parasitic diseases. However, the scientific basis of their use and toxicological profiles have not been assessed. We have, therefore, evaluated the antiplasmodial, antitrypanosomal, and cytotoxic activities of four African medicinal plant extracts namely, Anthonotha macrophylla leaf (AML), Annickia polycarpa leaf (APLE), Tieghemella heckelii stem bark (THBE), and Antrocaryon micraster stem bark (AMSBE) extracts in vitro against P. falciparum (W2mef laboratory strain), T. brucei (GUTat 3.1 strain), and mammalian RAW 264.7 macrophage cell line, respectively. The most active antiplasmodial extract was AML (IC50 = 5.0 ± 0.08 μg/mL with SI of 21.9). THBE also, produced the most effective antitrypanosomal activity (IC50 = 11.0 ± 0.09 μg/mL and SI of 10.2) among the extracts. In addition, none of the extracts produced toxic effect in the RAW 264.7 macrophage cell line except APLE which was moderately cytotoxic and also produced the least SI in both antitrypanosomal and antiplasmodial assays. These results suggest that AML and THBE could offer safe and alternative therapy for malaria and trypanosomiasis. This is the first study to report the antitrypanosomal and in vitro antiplasmodial activities of these four plants/plant parts. The cytotoxicity of the plant parts used is also being reported for the first time except for the T. heckelii stem bark.